Microarray-based genomic analysis identifies germline and somatic copy number variants and loss of heterozygosity in acute myeloid leukaemia - Ambayya @ Ampiah, A Angeli (2015)
Acute myeloid leukaemia (AML) is characterized by the overproduction of immature myeloid cells that accumulate in blood and bone marrow. While the specific cause of AML is usually unknown, several factors including chromosomal aberrations and genetic mutations have been implicated in the pathogenesis of this aggressive disease. Integration of genetic findings and clinicopathological information is crucial in establishing the diagnosis, prognosis and determining the therapeutic approach in the management of AML patients. The AML classification has evolved from morphology to cytogenetics/molecular genetics-based findings in recent years. Cytogenetic information is important in the detection of chromosomal abnormalities and has provided the framework for the diagnosis and risk-stratification in AML over the past decade. However, conventional cytogenetics is a technically demanding method. The success rate of chromosomal analysis is largely dependent on the availability of optimal and viable cells for culturing and the expertise with experience in identifying chromosomal aberrations at a limited resolution. Insights into molecular karyotyping using comparative genomic hybridization (CGH) and single nucleotide polymorphism (SNP) arrays enable the identification of copy number variations (CNVs) at a higher resolution and facilitate the detection of copy neutral loss of heterozygosity (CN-LOH) otherwise undetectable by conventional cytogenetics. The applicability of a customised CGH+SNP 180K DNA microarray with additional additional custom probes for 49 genes; every exon of eleven of these genes (TP53, DNMT3A, TET2, ASXL1, MLL,IKZF1, PAX5, EZH2, FLT3, NOTCH1 and ATM) was covered in the diagnostic evaluation of AML was assessed in this study. Paired tumour and germline (remission sample obtained from the same patient after induction) DNA were used to delineate germline variants in 41 AML samples. The prognosis based on karyotyping and molecular genetics was correlated with demographic (age, gender, ethnicity) and laboratory findings (WBC, aberrant antigen expression of CD2, CD4, CD7, CD19 and CD56). After comparing the tumour versus germline DNA, a total of 55 imbalances (n5-10 MB = 21, n 10-20 MB = 8 and n >20 MB = 26) were identified. Gains were most common in chromosome 4 (26.7%) whereas losses were most frequent in chromosome 7 (28.6%) and X (25.0%). CN-LOH was mostly seen in chromosome 4 (75.0%). Excellent agreements between the karyotype and CGH+SNP analyses were observed in 20 cases, with CGH+SNP analyses providing more precise breakpoint definition. Karyotype was not in agreement with CGH+SNP in 13 cases. In another three cases,array CGH+SNP detected aberrations which were missed by conventional karyotyping. Translocations were not detected by CGH+SNP in six cases. Correlation between prognosis on karyotyping and molecular genetics based on the clinical and laboratory findings showed statistically significant association between CD19 expression and a favourable prognosis. Statistically significant differences were observed between genders (P < 0.05 by Fisher‟s exact test); females had a more favourable prognosis compared to males. Chromosomal abnormalities with breakpoint coordinates were identified more accurately as compared to conventional cytogenetics with the use of the combined array CGH+SNP platform in this study. In summary, a combined platform of CGH+SNP provides invaluable insights into the elucidation of large spectrum of genomic aberrations in AML which may have prognostic implications.